SHORT- TIME EFFECTS OF BRONCHIAL ARTERY INFUSION WITH CHEMICAL DRUGS FOR LUNG CANCER - Yao, Yang; Pan, Yueyin; Li, Zhangjun; Zhu, Chi (Chinese Journal of Cancer Research, 2013)
Bronchial artery infusion (BM) with chemical agents was performed in 41 patients with lung carcinoma up to 61 times, included 33 cases (51 times) primary lmag cardmmm (PLC) and 8 cases (10 times) lung metastatic carcinoma (I2VIC). Short- time effects were valuable in 31 cases with PLC and 7 cases with LMC. Complete remission (CR) plus partial rimission (PR) ocurred in 14 cases (45.16%) among 31 patients with PLC and 1 case (14.28%) anmng 14 patients with LMC (P